The association between health literacy, private health insurance, and medical expenditure in South Korea - Jeehye Lee; Hye Sook Min; Dong-Hee Ryu (BMC Health Services Research)
Abstract Background Health literacy (HL) is crucial for effective healthcare utilization, but its relationship with private health insurance (PHI) enrollment and medical expenditure in South Korea remains unexplored. Objectives This study aimed to examine the associations between HL, PHI enrollment, and annual out-of-pocket (OOP) medical expenditure in South Korea's universal healthcare system. Methods Using data from the 2021 Korea Health Panel Study, we analyzed 5,469 participants aged 19–65. Logistic and multinomial logistic regression models were employed to assess factors influencing PHI enrollment. A Gamma GLM with a log- link function was used to examine the relationship between HL, PHI status, and OOP medical expenditure. Results Among participants, 70.05% had indemnity insurance coverage, and 88.02% held at least one PHI policy. Individuals with sufficient HL showed higher indemnity insurance enrollment (71.47%) compared to those with inadequate HL (63.17%). In unadjusted analyses, those with sufficient HL were more likely to have indemnity insurance (OR = 1.46, 95% CI: 1.19–1.80) and PHI policies. However, after adjusting for sociodemographic and health-related factors, these associations became non-significant. Individuals with indemnity insurance spent 36% more on OOP medical expenditure compared to those without (p < 0.01), and OOP medical expenditure increased with the number of insurance policies (39.1%, 71.6%, and 107.5% higher for one, two, and three or more policies, respectively, all p < 0.01). Those with sufficient HL spent 18.9% less on OOP medical expenditure compared to those with inadequate HL (p < 0.01). However, after adjusting for other variables, the coefficients lost statistical significance. After adjusting for other variables, higher education levels were associated with lower OOP medical expenditure. Conclusions While HL initially showed an association with PHI enrollment and reduced OOP medical expenditure, these relationships became non-significant after adjusting for socioeconomic and health-related factors. Higher education levels were associated with lower OOP medical expenditure, suggesting that educational attainment may better explain the observed HL effects. The positive association between PHI and OOP medical expenditure highlights the need for policy attention to ensure sustainable healthcare financing and appropriate medical service utilization in Korea's healthcare system.